Prevalensi Hiperkolesterolemia Pada Pasien Usia Remaja Di Laboratorium Klinik Thamrin Medan Tahun 2017 - Dinur Isna Faridha; Ida Fauziah; Mugi Mumpuni (Universitas Medan Area, 2019)
Hypercholesterolemia is a condition where cholesterol levels in the blood exceed normal limits and are a cause of risk of coronary heart disease. Generaly hypercholesterolemia occurs in old age but does not rule out the possibility that it can occur in adolescence. The purpose of this study was to determine the prevalence of hypercholesterolemia in adolescent patients in the Thamrin clinical laboratory in Medan 2017. This study was conducted in June 2018 with descriptive methods obtained by collecting secondary nomina from the results of the patient's laboratory examination. Based on the results of the study of the prevalence of hypercholesterolemia that occurred in adolescents as many as 123 people with a percentage of 17.7% of the number of adolescent patients who visited. The conclusion of this study is the state of hypercholesterolemia can occur in adolescents not only in adulthood and old age.